2020
DOI: 10.5194/gmd-13-5663-2020
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of spatial aerosol particle distributions to the boundary conditions in the PALM model system 6.0

Abstract: Abstract. High-resolution modelling is needed to understand urban air quality and pollutant dispersion in detail. Recently, the PALM model system 6.0, which is based on large-eddy simulation (LES), was extended with the detailed Sectional Aerosol module for Large Scale Applications (SALSA) v2.0 to enable studying the complex interactions between the turbulent flow field and aerosol dynamic processes. This study represents an extensive evaluation of the modelling system against the horizontal and vertical distr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 64 publications
0
28
0
Order By: Relevance
“…The idea is not to mainly validate the PALM model against experimental data but instead to systematically compare the nested-domain results to corresponding non-nested fine-and coarse-grid reference results and to show that the nested-domain solutions are closer to the fine-grid reference solutions than the coarse-grid reference solutions. PALM has been already evaluated for various ABL flows against measurement data (Letzel et al, 2008). Nevertheless, we show one comparison against wind tunnel data in Sect.…”
Section: Numerical Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea is not to mainly validate the PALM model against experimental data but instead to systematically compare the nested-domain results to corresponding non-nested fine-and coarse-grid reference results and to show that the nested-domain solutions are closer to the fine-grid reference solutions than the coarse-grid reference solutions. PALM has been already evaluated for various ABL flows against measurement data (Letzel et al, 2008). Nevertheless, we show one comparison against wind tunnel data in Sect.…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…Until recent years, there were no ABL LES models capable of modeling detailed surface structures, such as buildings or steep complex terrain shapes in the ABL. Nowadays, it is possible to carry out LES for complex built areas (e.g., Letzel et al, 2008), but this is still limited to relatively small areas because of the high spatial resolution requirement. Concerning urban LES, Xie and Castro (2006) have shown that at least 15 to 20 grid nodes are needed across street canyons to satisfactorily resolve the most im-portant turbulent structures within the canyons.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, most of the difficulties could be overcome by applying less elaborate methods in the current model. Based on smoothing analysis, Larsson et al (2005) give a condition for the optimal location of an uncoarsened plane in the case of an odd grid size. Galerkin coarse-grid approximation can result in a better approximation of the coarse-grid operator in this case, while discretization coarse-grid approximation can be more efficient for even-sized grid dimensions.…”
Section: Pressure Solutionmentioning
confidence: 99%
“…It was thus shown that turbulence at the stern of the ship may cause a significant decrease in exhaust pollutants, leading to higher concentrations near the ground and, most likely, higher exposure of the nearby urban population (Badeke et al, 2020). The application of LES Wolf-Grosse et al, 2017;Resler et al, 2020;Werhahn et al, 2020;, Khan et al, 2020 and CFD (San José et al, 2020;Gao et al, 2018;Flageul et al, 2020;Koutsourakis et al, 2020;Nuterman et al, 2011;Buccolieri et al, 2020, Kurppa et al, 2018Kurppa et al, 2019;Karttunen et al, 2020;Kurppa et al, 2020) models for air quality assessment in urban environments is becoming a frequent approach. Many papers implementing the PALM LES model (Maronga et al, 2015) have been presented at the 12 th…”
Section: Improved Turbulence and Dynamics For Higher Resolution Assessment Of Urban Air Qualitymentioning
confidence: 99%